A Savings Plan With Targeted Contributions. Issue 4 (6th August 2012) - Owadally, Iqbal; Haberman, Steven; Gómez Hernández, Denise
ABSTRACT We consider a simple savings problem where contributions are made to a fund and invested to meet a future liability. The conventional approach is to estimate future investment return and calculate a fixed contribution to be paid regularly by the saver. We propose a flexible plan where contributions are systematically adjusted and targeted. We show by means of stochastic simulations that this plan has a reduced risk of a shortfall and is relatively insensitive to errors in the planner's estimate of future returns. Sensitivity analyses in terms of parameter values, stochastic return models and investment horizons are also performed.